2020
DOI: 10.1126/sciadv.aba3126
|View full text |Cite
|
Sign up to set email alerts
|

Cavefish brain atlases reveal functional and anatomical convergence across independently evolved populations

Abstract: Environmental perturbation can drive behavioral evolution and associated changes in brain structure and function. The Mexican fish species, Astyanax mexicanus, includes eyed river-dwelling surface populations and multiple independently evolved populations of blind cavefish. We used whole-brain imaging and neuronal mapping of 684 larval fish to generate neuroanatomical atlases of surface fish and three different cave populations. Analyses of brain region volume and neural circuits associated with cavefish behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 63 publications
(108 reference statements)
7
51
0
Order By: Relevance
“…We have previously shown that treatment of cavefish with the beta‐adrenergic inhibitor propranolol restores sleep to cavefish, suggesting a critical role for enhanced norepinephrine signaling in cavefish (Duboué et al, 2012; J. Jaggard, Lloyd, Yuiska, et al, 2019). Our findings show some components of β‐adrenergic signaling are differentially expressed but the overall links to this pathway are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that treatment of cavefish with the beta‐adrenergic inhibitor propranolol restores sleep to cavefish, suggesting a critical role for enhanced norepinephrine signaling in cavefish (Duboué et al, 2012; J. Jaggard, Lloyd, Yuiska, et al, 2019). Our findings show some components of β‐adrenergic signaling are differentially expressed but the overall links to this pathway are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…To study changes in the function of the optic tectum in A. mexicanus, we generated surface and cave populations harboring the genetically encoded Ca 2+ indicator (GCaMP6s) of the pan-neuronal promoter elavl3/HuC (37). The surface and Molino populations have previously been described (6); here, we also utilizea HuC:GCaMP6s Pachón line, allowing for direct comparison of brain function in independently evolved cavefish populations. Fish from the surface, Pachón, and Molino populations expressed the reporter as early as 1.5 dpf through 8.5 dpf (Fig 1B…”
Section: Development Of Transgenic Cavefish For Brain Imagingmentioning
confidence: 99%
“…In sighted species, visual processing within the tectum is essential for generating appropriate visuomotor behaviors including prey capture and predator avoidance (21)(22)(23). In comparison to surface fish, the size of the tectum is reduced in cavefish from multiple populations, revealing co-evolution of reduced inputs of the retina and its target centers within the brain (6). Recently, we generated a quantitative neuroanatomical atlas of surface fish and multiple cavefish populations that revealed that despite eye loss, the optic tectum is only reduced by ~20% across populations, raising the possibility that this brain region has been repurposed for functions other than vision (6,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one of the main unsolved questions is how gene expression and morphogenesis are coordinated (that is, the generation and maintenance of multiple cell types, in highly organized spatial patterns during brain embryonic development). Existing gene expression and marker atlases in fish provide valuable tools (Chow et al, 2020; Jaggard et al, 2020; Ronneberger et al, 2012; Tabor et al, 2019), but they typically have some limitations in addressing the question of spatiotemporal coordination, including: i) they are based on images from fixed samples acquired at late developmental stages and aligned through non-rigid registration, which is suboptimal for morphogenesis studies; ii) they use filters and are unable to quantify patterns, partially due to the lack of a standardized quantification method; iii) accessing the data is difficult; iv) user-upgrades are difficult, as data usually need to be sent to the atlas-makers for processing; v) atlases are usually hosted on individual platforms, making access to the data challenging; and vi) they lack 3D quantifications. Here, we developed a new “atlas-builder” pipeline that overcomes most of these limitations and can be used to create an expandable atlas of any tissue in any organism.…”
Section: Introductionmentioning
confidence: 99%